Characterizations of palace lantern tassels preserved in The Palace Museum, Beijing, by UPLC‐ESI‐Q‐TOF. (17th February 2020) - Zhang, Y.; Wei, L.; Cui, Z.; Zhang, T.; Lei, Y.; Gu, A.; Chen, Y.; Zhang, L. Y.; Du, Z. X.
Abstract : Palace lanterns were important and highly visible decorations in the imperial palace in Beijing, China, during the Qing dynasty (1636–1912). Most lanterns had colourful tassels made of fibres. The study performed a comprehensive investigation of the materials and dyes used for palace lantern tassels preserved in The Palace Museum, Beijing. Eight samples with different colours, including yellow, green and red, from five palace lanterns were analysed. By using ultra‐performance liquid chromatography combined with time‐of‐flight mass spectrometry, the compositions of the dyes were identified quickly, and thus the dyes' origins were explored. A X‐ray fluorescence spectrometer assisted in the detection of whether a mordant was used during the dyeing process. As a result, the tassels were all made of silk, discovered through the use of microscopic observation and micro‐Fourier transform infrared spectrometry analysis. Different dyeing techniques were found in these tassels: yellow tassels were dyed by cork tree or turmeric by a direct dyeing method; greens were dyed by pagoda bud with an iron mordant, or by the combination of cork tree and indigo using multi‐dyeing method; and red tassels were coloured with different acid red industrial dyes. These results provide valuable data for the conservation of ancient textile tassels and contribute to the investigation of other hanging tags.